Histological Structure of Broiler Duodenum After Feeding a Combination of Additives Spirulina Flour and Liquid Nanochitosan - Nabila Syalist Fitria; Sunarno; Kasiyati; Muhammad Anwar Djaelani (Al-Kauniyah: Jurnal Biologi, 2026)
Spirulina is a microalgae rich in protein, fat, carbohydrates, minerals, chlorophyll a, phycocyanin, beta-carotene, linoleic acid, and vitamins. Nanochitosan, a polymer derived from chitin, contains amine and carboxylate groups. Both additives enhance digestion, absorption, and duodenal structure in broilers. This study analyzed the effect of combining spirulina flour and liquid nanochitosan on broiler duodenal histology. A 3 × 2 factorial completely randomized design (CRD) with four replicates was used. The first factor was spirulina flour (0; 3; 6%), and the second was liquid nanochitosan (0 & 5%). Measured variables included duodenal weight, length, villus height, epithelial thickness, muscular layer thickness, and lumen diameter. Data were analyzed using ANOVA at a 5% significance level. Results showed spirulina alone affected duodenal lumen diameter (P <0.05), while nanochitosan alone had no effect on duodenal length, villus height, epithelial thickness, muscular thickness, or lumen diameter (P >0.05). The combination significantly increased duodenal weight (P <0.05) but did not affect other variables. In conclusion, spirulina and nanochitosan improve duodenal weight but do not alter duodenal length, duodenal lumen diameter, villus height, or layer thicknesses.